Decision Support System for Land Suitability Assessment of Horticultural Crops of Legume Commodities Using AHP-VIKOR - Ilham Sahputra; Rizky Putra Phonna; Natasya Natasya; Annisa Karima; T. Sukma Achriadi Sukiman (Universitas Mulia, 2024)
This Decision Support System (DSS) is designed to evaluate land suitability for horticultural crops, specifically legumes, using a combination of Analytical Hierarchy Process (AHP) and VIKOR (Vise Kriterijumska Optimizacija I Kompromisno Resenje) methods. The system aids farmers in determining the appropriate crops based on the available land conditions. The research includes problem identification, literature review, data collection, and system design. The implementation of the AHP-VIKOR methods has proven effective and accurate in providing horticultural crop recommendations. This system adds value to modern and efficient agricultural land management. The research results show that the AHP-VIKOR methods successfully applied in determining the suitability of land for legumes in the areas of Bireun, Bukit Rata, Sawang, and Pesisir Pelabuhan Kreung Geukuh with satisfactory outcomes. Therefore, the AHP-VIKOR methods are considered optimal for weighting criteria and ranking alternatives in selecting land for legume crops